(untitled) (Indonesian Journal of Agrarian Law, 2026)
Sand Dunes are a unique natural phenomenon, especially in tropical regions such as Indonesia. Their existence has led some communities to establish buildings and economic activities for their livelihoods. These buildings and activities certainly threaten the sustainable existence of the sand dunes, thus requiring serious responses and efforts from policymakers. This study examines the conflict of interest between the local government and the Parangtritis community in the utilization of the Parangtritis Sand Dunes. The method used is empirical juridical, which combines the analysis of legal norms with social reality in the field. Primary data used are interviews with related parties, namely the Bantul Regency Government and the community around the core zone. The research results show that land tenure carried out by the community is not based on legitimate rights under Law Number 13 of 2012 and the Regulation of the Governor of the Special Region of Yogyakarta Number 33 of 2017. Buildings and activities frequently carried out in the core zone also threaten the existence of the dunes and obstruct the wind flow that carries sand material. This study finds that community collaboration and awareness for sustainable environmental utilization are necessary to prevent the extinction of the Parangtritis Sand Dunes.